2019
DOI: 10.1007/s00249-019-01355-6
|View full text |Cite
|
Sign up to set email alerts
|

Critical parameters maintaining authentic CRAC channel hallmarks

Abstract: Ca 2+ ions represent versatile second messengers that regulate a huge diversity of processes throughout the cell's life. One prominent Ca 2+ entry pathway into the cell is the Ca 2+ release-activated Ca 2+ (CRAC) ion channel. It is fully reconstituted by the two molecular key players: the stromal interaction molecule (STIM1) and Orai. STIM1 is a Ca 2+ sensor located in the membrane of the endoplasmic reticulum, and Orai, a highly Ca 2+ selective ion channel embedded in the plasma membrane. Ca 2+ store-depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 137 publications
(349 reference statements)
1
43
0
Order By: Relevance
“…Several single point mutants of Orai1, containing amino acid substitutions, in distinct TM regions, have already been reported to display constitutive activity 32,36,41,43,[45][46][47][50][51][52] . This led to the hypothesis that Orai channel opening is controlled by several critical sites within all four TM regions 35,36,46,51,55,56 . We screened residues in TM2/3 and 4 via single point mutations, with the focus on those located in close proximity (2 -4 Å) within one or between two adjacent Orai subunits (Table 2, 3; include distances estimated via Pymol in the hOrai1 model 46,57 based on the X-ray structure of the closed dOrai PDB ID: 4HKR).…”
Section: Resultsmentioning
confidence: 99%
“…Several single point mutants of Orai1, containing amino acid substitutions, in distinct TM regions, have already been reported to display constitutive activity 32,36,41,43,[45][46][47][50][51][52] . This led to the hypothesis that Orai channel opening is controlled by several critical sites within all four TM regions 35,36,46,51,55,56 . We screened residues in TM2/3 and 4 via single point mutations, with the focus on those located in close proximity (2 -4 Å) within one or between two adjacent Orai subunits (Table 2, 3; include distances estimated via Pymol in the hOrai1 model 46,57 based on the X-ray structure of the closed dOrai PDB ID: 4HKR).…”
Section: Resultsmentioning
confidence: 99%
“…Many of the gain-offunction mutants have reduced ion selectivity for Ca 2+ , as indicated by an altered electrophysiological current-voltage relationship. The H134A mutant of human Orai1, on the other hand, is highly selective for Ca 2+ and exhibits a similar current-voltage relationship to that of the wild type channel when it is activated by STIM, which suggests that the pore adopts a similar conformation to the STIM-activated channel (Frischauf et al, 2017;Krizova et al, 2019;Yeung et al, 2018). Biochemical studies, supported by molecular dynamics simulations, also suggest that the conformation of the H134A mutant is highly similar to the naturally opened channel (Frischauf et al, 2017;Yeung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…STIM proteins (STIM1 and STIM2 in humans) are single-pass membrane proteins located in the membrane of the ER, and following Ca 2+ depletion from the ER regulate Orai channel function (Roos et al, 2005; S. L. Zhang et al, 2005). Although the molecular mechanisms of this process are not yet fully resolved, a scheme for channel activation is becoming clear (reviewed in (Krizova, Maltan, & Derler, 2019; Lunz, Romanin, & Frischauf, 2019; Qiu & Lewis, 2019)). The “inside-out” signaling from the ER to the plasma membrane occurs at cellular locations where the ER and plasma membranes are close together (separated by ∼ 10-20 nm).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mutation of a pore-lining residue (R91W) in Orai1 causes a severe combined immune deficiency-like disorder due to lack of functional CRAC channels in the T cells of these patients (Feske et al, 2006). In addition to loss-of-function mutations, some gain-of-function mutations have been identified that allow Orai to conduct cations without activation by STIM (reviewed in (Krizova et al, 2019)). Activating mutations of Orai1 have been associated with tubular aggregate myopathy and Stormorken syndromes (Lacruz & Feske, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation